Emerging strategies for environmental decontamination of the nosocomial fungal pathogen Candida auris. Issue 6 (10th June 2022) - Bandara, H. M. H. N.; Samaranayake, L. P.
Abstract : Candida auris is a recently emerged multidrug-resistant fungal pathogen that causes life-threatening infections to the human population worldwide. Recent rampant outbreaks of C. auris in coronavirus disease 2019 (COVID-19) patients, together with outbreaks in over 45 countries, highlight its threat to patients and healthcare economies. Unlike other pathogenic Candida species, C. auris is capable of surviving in abiotic surfaces of healthcare facilities for prolonged periods, leading to increased risk of transmission within nosocomial settings. C. auris is resistant to multiple classes of antifungal agents, forms dry biofilms and transmits independently to regional epicentres, making its eradication from nosocomial environment arduous. The lack of strategies for environmental decontamination of C. auris from nosocomial settings is evident from the generic guidance and recommendations provided by leading global healthcare bodies. Therefore, this minireview discusses the current guidelines for environmental decontamination of C. auris and compounds and strategies currently under investigation for potential future use. While established guidelines recommend the use of products mainly consisting of sodium hypochlorite and hydrogen peroxide, initial works have been reported on the promising anti- C. auris properties of various other compounds and some biocompatible alternatives. Further validation of these approaches, coupled up with environmentally friendly decontamination protocols, are warranted to achieve superior elimination of C. auris from healthcare settings.